A new optimisation approach for the driver restraint system for the frontal impact of a mini-bus. (6th October 2008) - Yi, Lin; Hailin, Liu; Junyuan, Zhang
Occupant restraint system design is very important for passenger vehicles to improve passive safety performance. In this paper, an optimisation approach using MADYMO simulation is put forward for occupant restraint system design. Based on multi-body dynamics theory and the finite element method, an occupant restraint system model is built for the driver protection in a mini-bus subject to frontal impact. The model validation is also considered against the full size impact test. Then, a new parameter optimisation approach, called the three-step optimisation method, is proposed and applied to the model established. Simulations are conducted to investigate the system performance. The results indicate significant safety performance improvements for the mini-bus occupant restraint system.